Revision der Gattung Hexaurus Reitter, 1884 (Coleoptera, Cholevidae, Bathysciinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Hexaurus, an endemic genus of the Central Stara Plania [Balkan mountains] is characterized by diagnostic features and redescribed. Its systematic position cannot be marked exactly, because of the lack of a modern phylogenetic system in Bathysciinae. Redescriptions are given and lectotypes designated for both Bathysciinae. Redescriptions are given and lectotypes designated for both Hexaurus merklii (Frivaldszky, 1879) and Hexaurus similis (Frivaldszky, 1879). A lectotype is also designated for Hexaurus merklii var. affinis (Frivaldszky, 1879) which is a synonym of H. merklii. Two new species, Hexaurus schipkaensis sp. n. and Hexaurus paradisi sp. n., are described. A key to the species is enclosed. The genus and its subtaxa are established as monophyla. A phylogenetic diagram is given. Nomenclatural Acts merklii (Frivaldszky, 1879) (Hexaurus), Lectotype described as Pholeuon merklii paradisi Zerche, 1990 (Hexaurus), spec. n. schipkaensis Zerche, 1990 (Hexaurus), spec. n. similis (Frivaldszky, 1879) (Hexaurus), Lectotype described as Pholeuon merklii var. simile affinis (Frivaldszky, 1879) (Hexaurus merklii), Lectotype described as Pholeuon merklii var. affine